A Systematic Review of Tyrosine Kinase Inhibitor on Osteosarcoma Patient: The Hope of Decades-long Struggle? - Sampe, Samuel Hobarto; Suriasa, Deodatus Theodorus; Rante, Su Djie To (http://dharmais.co.id/, 2025)
Background: Osteosarcoma, a very aggressive tumor, is the most common malignant bone tumor in all ages, mainly affecting children and adolescents. For the last 40 years, we haven’t seen any real breakthrough in treatment modalities, as a result, the current survival rate and outcome of osteosarcoma have remained stagnant since the 1980s. Currently, tyrosine kinase inhibitor (TKI), as a part of targeted therapy and precision medicine, has emerged as a potential treatment modality. We conducted a systematic review to evaluate its efficacy and safety on osteosarcoma.Methods: A comprehensive search of multiple scientific databases such as PubMed, CENTRAL, ScienceDirect, and Scopus was conducted up to February 2024. The selection process included all retrievable clinical trials of TKIs in osteosarcoma patients. Results: Nine studies involving 288 patients were finally evaluated. TKIs show clear efficacy in advanced osteosarcoma. All TKIs tested were able to surpass the standard of median progression-free survival (PFS) of more than 4 months and were considered to have positive outcomes. It is also shown that TKIs will perform even better in combination with other chemotherapeutic agents. In terms of safety, the majority of adverse events are mild (grade I - II), and serious adverse events are manageable. There were no treatment-related deaths, further indicating the well-tolerability of TKIs. Conclusions: This systematic review shows that TKI is a promising therapeutic modality for patients with advanced osteosarcoma. Adverse events of TKIs are mostly mild, and manageable. TKIs may be the hope of our decades-long effort to discover a novel therapy and increased survivability of advanced osteosarcoma.